The use of scaffolding technique via Facebook in improving descriptive writing among ESL learners - Abdul Hameed Abdul Majid,; Siti Hamin Stapa, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Learners today anticipate some form of blended instruction using technology. This study investigated the effectiveness of scaffolding writing using Facebook in a blended learning ESL class. A qualitative study was chosen to gather data from the subjects from a rural secondary school in Malaysia. The subjects were divided into experimental and control groups. The study then continued for 12 weeks beginning with a pre-test for both groups. The experimental group (blended learning class) went through traditional instruction in the classroom and scaffolding using Facebook after school hours. The control group went through only traditional classroom instruction. A post-test was administered at the end of 14 weeks to determine the effects of the treatment on the experimental group. All essays written by the participants in both groups in the pre-test and post-test were examined in order to see the difference in the ability to produce descriptive patterns. The findings revealed that the participants favoured the use of blended learning as a learning method compared to mere traditional strategy. They also opined that scaffolding-using Facebook enabled them to learn better and improve their writing process and writing performance. Content analysis on the essays written by participants revealed a marked improvement among the experimental group. The implications of this study suggest that Facebook or any online platform should be integrated in the teaching and learning of writing in the ESL classroom.